Using vocational education to support development solutions in the Pacific: An emphasis on climate change and health. Issue 2 (2nd April 2020) - Hausia Havea, Peni; Siga, Amelia; Rabuatoka, Titilia; Tagivetaua Tamani, Apenisa; Devi, Priya; Senikula, Ruci; Hemstock, Sarah L; Jacot des Combes, Helene
Abstract: In this article, author(s) reported on the results of the EU PacTVET project, which explored the use of TVET to support resilience in the region with an emphasis on climate change and health. An exploratory design was used to investigate how vocational education supports solutions for climate change and health. The results showed that vocational education plays a significant role in building safety and resilience of people in the region. Most significantly, getting an accredited qualification on health resilience and/or job in the health sector may help them to respond to climate change effectively and efficiently.